The - Powell, Jim (Oxford University Press, 2007)
Jim Powell's translations represent a unique combination of poetic mastery in English verse and a deep schlolarly engagement with Sappho's ancient Greek. They are incomparably faithful to the literal sense of the Greek poems and, simultaneously, to their forms, preserving the original meters and stanzas while exactly replicating the dramatic action of their sequences of disclosure and the passionate momentum of their sentences. Powell's translations have often been anthologized and selected for use in textbooks, winning recognition among discerning readers as by far the best versions in English